Alternative splicing variant of RHBDD2 is associated with cell stress response and breast cancer progression - Canzoneri, Romina (2018)
RHBDD2 is an intramembrane pseudoprotease member of the Rhomboid superfamily. Our previous studies in breast and colorectal cancer indicate an association between RHBDD2 overexpression and advanced tumor stages. Two alternative transcriptional variants have been described for RHBDD2, which would be encoding for different RHBDD2 protein isoforms. The expression of these RHBDD2 variants/isoforms and its association with breast cancer was the focus of this study. First, expression of RHBDD2 splicing variants was evaluated in normal and breast tumor samples. RHBDD2 variant 2 overexpression was detected in tumors in respect to normal breast tissues at the mRNA and protein levels (P<0.05). Moreover, RHBDD2 variant 2 expression was associated with poor prognostic factors such as basal-like intrinsic subtype (P<0.05), high proliferation (P<0.01) and long-term risk-of-recurrence (P<0.01) scores. Second, the expression of both variants was evaluated under nutritional-deprived conditions in breast cancer cell lines. Results demonstrated that RHBDD2 splicing was switched from mRNA variant 1 to variant 2 in association with a significant increment of protein isoform B in response to glucose starvation treatment. Therefore, we propose that the switch from the RHBDD2 variant 1, expressed in normal epithelial cells, to variant 2 occurs as an adaptive phenotype to bypass the stressful tumor microenvironment and promote tumor progression. Finally, the RHBDD2 subcellular localization was corroborated at the Golgi apparatus and their associated v-SNARE transport vesicles, suggesting a putative new role for RHBDD2 in the protein trafficking of human breast cancer cells.